Pengembangan Media Interaktif Berbasis iSpring Presenter pada Materi Bahasa Arab Madrasah Ibtidaiyah - Risa Gowwiyuningsih (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2023)
The use of learning media that has been applied so far still has various shortcomings, both in terms of design, material, and language. Based on these problems, the author formulates the research problem, namely: